Performance appraisal: what is wrong with it ? - Lee, Nagarajah (Universiti Teknologi MARA, Sarawak, 2004)
An organization will enjoy a sustained performance only if it creates a performance culture among its employees. This is only possible when the performance management system is tailored to the organization so that it will align itself to the organization's culture. A local perspective of the organization, such as the context in which it exists, needs to be integrated with the generic principles of performance management so that the effectiveness of its implementation is optimal. In most performance management model the performance appraisal is the most visible component of the performance, management process. Thus, many people perceived performance appraisal as the performance management system itself where in actual fact the annual performance appraisal is only one component of the performance management process. The misconception of equating performance management with performance appraisal has been the major factor which prevents the performance management system from being a tool for sustaining the success and competitiveness of the organization. Bob Havard (2001) stated that the performance appraisal system that functions as a stand-alone tool for managing the employees' performance will eventually degenerate if it is not connected to other performance management process.